Innodiging voor mooie tentoonstellingen + trio eenzaamheid. - Andriesse, Paul; Baer, Jo; Bloemheuvel, Marente; Fuchs, Rudi H.; Gudmundsson, Sigurdur; Loock, Ulrich; Visch, Henk (Amsterdam : Galerie Paul Andriesse, 1989)
Oehlen, Albert ; Daniels, René ; Visch, Henk ; Dumas, Marlene ; Büttner, Werner ; Andriesse, Erik ; Mol, Pieter Laurens ; Houshiary, Shirazeh ; Heller, Susanna ; Wentworth, Richard ; Geelen, Guido ; Baer, Jo ; Gudmundsson, Sigurdur ; Denée, Michel ; Chamberlain, John ; Ungers, Sibylle ; van de Ven, Lidwien
+ overzicht tentoonstellingen 1984-1989
Nederlands & Engels & Duits
boek